CRISPR/Cas9-mediated ELANE knockout enables neutrophilic maturation of primary hematopoietic stem and progenitor cells and induced pluripotent stem cells of severe congenital neutropenia patients - Nasri, Masoud (Haematologica, 2020)
A Autosomal-dominant ELANE mutations are the most common cause of severe congenital neutropenia. Although the majority of congenital neutropenia patients respond to daily granulocyte colony stimulating factor, approximately 15 % do not respond to this cytokine at doses up to 50 μg/kg/day and approximately 15 % of patients will develop myelodysplasia or acute myeloid leukemia. “Maturation arrest,” the failure of the marrow myeloid progenitors to form mature neutrophils, is a consistent feature of ELANE associated congenital neutropenia. As mutant neutrophil elastase is the cause of this abnormality, we hypothesized that ELANE associated neutropenia could be treated and “maturation arrest” corrected by a CRISPR/Cas9-sgRNA ribonucleoprotein mediated ELANE knockout. To examine this hypothesis, we used induced pluripotent stem cells from two congenital neutropenia patients and primary hematopoietic stem and progenitor cells from four congenital neutropenia patients harboring ELANE mutations as well as HL60 cells expressing mutant ELANE. We observed that granulocytic differentiation of ELANE knockout induced pluripotent stem cells and primary hematopoietic stem and progenitor cells were comparable to healthy individuals. Phagocytic functions, ROS production, and chemotaxis of the ELANE KO (knockout) neutrophils were also normal. Knockdown of ELANE in the mutant ELANE expressing HL60 cells also allowed full maturation and formation of abundant neutrophils. These observations suggest that ex vivo CRISPR/Cas9 RNP based ELANE knockout of patients’ primary hematopoietic stem and progenitor cells followed by autologous transplantation may be an alternative therapy for congenital neutropenia.